Pemberian ASI Eksklusif Berhubungan dengan Pertumbuhan Gigi dan Perkembangan Motorik Kasar pada Bayi Usia 6-18 Bulan - Aninda Rusmin; Retno Setyo Iswati; Desta Ayu Cahya Rosyida (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKes Banyuwangi, 2024)
The low level of exclusive breastfeeding in Indonesia needs attention. This is related to chronic malnutrition related to tooth growth and motor development, which indirectly impacts the quality of human resources. The 6 month period of life will determine the quality of the child in the future. This study aims to determine the relationship between exclusive breastfeeding and tooth growth and gross motor development in babies aged 6-18 months in Sidoarjo, Krian district. This research uses a quantitative type of research with a cross-sectional approach. The population in this study were babies aged 6-18 months. The research used total sampling. The data used in this research is primary data using a questionnaire instrument for breastfeeding history and tooth growth, while gross motor development data uses the KPSP (Pre-Screening Questionnaire) instrument and the research sample is babies and the sample size is 49 babies. The independent variable is exclusive breastfeeding and the dependent variable is tooth growth and gross motor development. Data analysis used the chi square test. The results of this study indicate that there is a relationship between exclusive breastfeeding and tooth growth and motor development in babies aged 6 to 18 months. The research results also concluded that there was only a relationship between breastfeeding and tooth growth in babies aged 6 to 18 months with a P-value of 0.008 and motor development in babies aged 6 to 18 months with a P-value of 0.000.